Agribusiness Partnerships and Inclusive Governance for Equitable Farmer Welfare - Hannin Pradita Nur Soulthoni; Eka Suaib; Lestari Widiawati; Sitti Harnia (UIN Sunan Gunung Djati, 2026)
This study examines the agribusiness partnership between PT Hikmahfarm and farmers in Pangalengan, Bandung Regency, Indonesia, focusing on its effectiveness and inclusivity as a poverty alleviation strategy. Farmers face persistent structural challenges, including land scarcity, limited access to capital, low technology adoption, and unequal market access. This research employs a descriptive qualitative approach, using in-depth interviews with 25 purposively selected informants, field observations, and document analysis. Data were analyzed thematically using NVivo software. The findings show that the partnership effectively improves access to capital, technology, and markets for partner farmers, resulting in increased productivity and income stability. However, these benefits are not accessible to non-partner farmers, creating a two-tiered system that risks widening socio-economic disparities. The study reveals that the partnership reflects an incomplete form of collaborative governance due to its limited inclusivity. This research contributes empirically by demonstrating that agribusiness partnerships can simultaneously promote empowerment and exclusion. It highlights the need for proactive government intervention to strengthen public institutions and ensure more inclusive partnership models. Such efforts are essential to transform agribusiness partnerships into a more equitable and systemic poverty alleviation strategy aligned with the Sustainable Development Goals’ principle of leaving no one behind.